2021
DOI: 10.1039/d1cp02220b
|View full text |Cite
|
Sign up to set email alerts
|

Screening of transition metal doped copper clusters for CO2 activation

Abstract: Activation of CO2 is the first step towards its reduction to more useful chemicals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 97 publications
3
24
0
Order By: Relevance
“… 34 Apart from atomic ions, CO 2 activation was also studied in clusters of selected metals. 35 42 In line with the above, for cationic Cu n + clusters only nonactivated adsorption was observed, substantiated by large calculated reaction barriers hindering the activation. 41 For anionic clusters, size-selective CO 2 activation was observed for Pt n – , Co n – and C-doped Cu n – clusters, 36 , 39 , 40 whereas for neutral Cu clusters, doping with 3d elements was computationally shown to allow control over activation.…”
Section: Introductionsupporting
confidence: 81%
“… 34 Apart from atomic ions, CO 2 activation was also studied in clusters of selected metals. 35 42 In line with the above, for cationic Cu n + clusters only nonactivated adsorption was observed, substantiated by large calculated reaction barriers hindering the activation. 41 For anionic clusters, size-selective CO 2 activation was observed for Pt n – , Co n – and C-doped Cu n – clusters, 36 , 39 , 40 whereas for neutral Cu clusters, doping with 3d elements was computationally shown to allow control over activation.…”
Section: Introductionsupporting
confidence: 81%
“…[7][8][9][10][11] Gas phase clusters well-defined composition and precise geometric structure are perfect model systems to investigate the reactions taking place at the active sites of complex catalyst. [12][13][14] These model systems made it possible to understand the structure -effect correlations in reaction mechanism regarding cluster size [15][16], geometry [17][18], dopant [19][20], and charge state [12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work we investigated differently charged copper clusters reactions with CO2 and CO2 + H2, and we could not exclude or confirm the H2 dissociation due to the absence of characterization methods. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] To analyze elementary steps in different conditions a microkinetic model is needed. Master equation is a well-used model for combustion reaction [35], and can form a bridge between calculations and experiments, due to their validity on different pressure ranges.…”
Section: Introductionmentioning
confidence: 99%
“…1 Significant efforts are being made toward the improvement of copper-based catalysts. 7,8 New catalysts are being explored simultaneously. In 2012-2015, our group found that In 2 O 3 has outstanding activity with high methanol selectivity for CO 2 hydrogenation by using density functional theoretical (DFT) calculations 9,10 and experimental studies.…”
Section: Introductionmentioning
confidence: 99%